2010
DOI: 10.1111/j.1469-0691.2010.03083.x
|View full text |Cite
|
Sign up to set email alerts
|

High cytokine levels in perforated acute otitis media exudates containing live bacteria

Abstract: Acute otitis media (AOM) is an inflammatory response to microbes in the middle ear, sometimes associated with rupture of the tympanic membrane. Human leukocytes produce different patterns of inflammatory mediators in vitro when stimulated with Gram-positive and Gram-negative bacteria, respectively. Here, we investigated the cytokine and prostaglandin E2 (PGE2) responses in middle ear fluids (MEFs) from children with spontaneously perforated AOM, and related the mediator levels to the presence of pathogens dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…The role and requirement for IL-8 in chemotaxis for neutrophil recruitment during recurrent infections have been described in other studies that involved other disease conditions. 30,31 We found fourfold higher levels of SLPI gene expression in children who were sOP. SLPI is generally expressed at mucosal surfaces and plays a role in the defense against the destruction of epithelial tissues by neutrophil elastase.…”
Section: Discussionmentioning
confidence: 71%
“…The role and requirement for IL-8 in chemotaxis for neutrophil recruitment during recurrent infections have been described in other studies that involved other disease conditions. 30,31 We found fourfold higher levels of SLPI gene expression in children who were sOP. SLPI is generally expressed at mucosal surfaces and plays a role in the defense against the destruction of epithelial tissues by neutrophil elastase.…”
Section: Discussionmentioning
confidence: 71%
“…Although this study focused on children with AOM in which the tympanic membrane ruptured spontaneously, it is important to note that they also found an association between the presence of bacteria and increased levels of cytokines. 27 Thus, both their and our study point to an important role for bacteria in the inflammatory cytokine response during OM. In contrast to the study by Skovsberg et al, we also assessed the impact of bacterial load on the cytokine response.…”
Section: Discussionmentioning
confidence: 75%
“…However, the present study found a statistically significant higher risk of OM when rod‐shaped bacteria were present together with inflammatory cells. The presence of inflammatory cells indicates an active immune response, and human studies have shown that an excessive production of proinflammatory cytokines, particularly in the presence of bacteria, can cause damage to the TM . The majority of rod‐shaped bacteria were Pseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of inflammatory cells indicates an active immune response, and human studies have shown that an excessive production of proinflammatory cytokines, particularly in the presence of bacteria, can cause damage to the TM. 28,29 The majority of rod-shaped bacteria were Pseudomonas spp. which are known to form biofilms.…”
Section: Discussionmentioning
confidence: 99%